2007
DOI: 10.1152/jn.00106.2007
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Currents Prior to Onset of Epileptiform Activity in Rat Microgyria

Abstract: Zsombok A, Jacobs KM. Postsynaptic currents prior to onset of epileptiform activity in rat microgyria. J Neurophysiol 98: 178 -186, 2007. First published May 2, 2007 doi:10.1152/jn.00106.2007. Structural malformations of the cortex, arising as a result of genetic mutation or injury during development are associated with dyslexia, epilepsy, and other neurological deficits. We have used a rat model of a microgyral malformation to examine mechanisms of epileptogenesis. Our previous studies showed that the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…Importantly, later studies went on to show that increased excitatory input onto layer V pyramidal cells is present before the onset of epileptiform activity. This supports the hypothesis that network level changes occur during the latent period, before the onset of hyperexcitability at P14 (Zsombok & Jacobs, 2007). Changes in glutamate receptor expression and localization have also been reported in the FL model (Hagemann et al, 2003; Defazio & Hablitz, 2000; Zilles et al, 1998).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Importantly, later studies went on to show that increased excitatory input onto layer V pyramidal cells is present before the onset of epileptiform activity. This supports the hypothesis that network level changes occur during the latent period, before the onset of hyperexcitability at P14 (Zsombok & Jacobs, 2007). Changes in glutamate receptor expression and localization have also been reported in the FL model (Hagemann et al, 2003; Defazio & Hablitz, 2000; Zilles et al, 1998).…”
Section: Introductionsupporting
confidence: 87%
“…These changes may both drive later hyperexcitability and be useful targets for therapeutic intervention. We and others have shown that increases in EPSCs occur in the neonatal FL cortex by P7-P11 (Zsombok & Jacobs, 2007). This is in line with the hypothesis that increased excitatory input occurs during the latent period and may drive later hyperexcitability.…”
Section: Discussionmentioning
confidence: 80%
“…To confirm that excitatory hyperinnervation could be a cause rather than a result of hyperexcitability, we have previously examined whether it occurred prior to or after the onset of network hyperexcitability at P12. We found that there was an abrupt and consistent increase in the frequency of mEPSCs in PMR pyramidal neurons on P10 (Zsombok and Jacobs, 2007). When neonatally freeze-lesioned animals are given a second hit via hyperthermia on P10, they develop spontaneous seizures as adults (Scantlebury et al, 2005).…”
Section: Introductionmentioning
confidence: 64%
“…Our findings are in contrast to studies in rodent malformation models 13,14,16 and human epileptic patients with heterotopia or focal cortical dysplasia 12,27,28 in which alterations in postsynaptic NMDA-type glutamate receptor subunit expression or function were reported. However, in a rodent model of polymicrogyria 20,29 and both the kainate and pilocarpine models of TLE, 18,19,30 a similar increase in EPSC frequency was observed, suggesting that enhanced excitatory drive may be a common feature of the epileptic brain.…”
Section: Discussionmentioning
confidence: 85%